Feasibility and performance of a thin-film composite seawater reverse osmosis membrane fabricated on a highly porous microstructured support - Lim, Yu Jie (2022)
Although a highly porous support membrane has attracted increasing attention as an alternative to enhance the water permeability of a thin-film composite (TFC) membrane without compromising salt rejection, its feasibility has not ever been tested in seawater desalination. This study explored the availability and potential of a highly porous microstructured (HPμS) support membrane as a support for a seawater reverse osmosis (SWRO) membrane. Our lab-made membranes, TFC-HPμS, exhibited a higher water permeability of 1.62 L m−2 h−1 bar−1 as compared with most of the state-of-the-art SWRO membranes recently reported in the literature, while achieving comparable NaCl rejection (99%) in SWRO test condition (55 bar, 35,000 mg L−1 of NaCl). This excellent performance is thought to stem from the HPμS support endowing a TFC membrane with comparable mechanical properties to that of existing support used for conventional SWRO membrane and shortened effective diffusion pathway of water molecules over the active layer. The robustness and enhanced mechanical strength of the TFC-HPμS membrane are attributed to its narrow and regularly arranged finger-like structure ensuring the even distribution of local stresses, thereby eliminating the presence of stress convergence points. The shortened effective diffusion pathway was estimated to be achieved mainly by less localized surface pores due to the HPμS support's highly porous surface with a larger number of even distributed surface pores. This study potentially opens up another workable pathway in the fabrication of SWRO membranes with enhanced performance without significant sacrifice of the selectivity.